PENERAPAN STRATEGI PEMBELAJARAN HOLLYWOOD SQUARES UNTUK MENINGKATKAN PENGUASAAN KONSEP FISIKA SISWA KELAS XI IPA SMA NEGERI 14 PEKANBARU PADA MATERI USAHA DAN ENERGI - Nopian, Joni; ', Fakhruddin; ', Hendar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to describe the concepts achievement of physics and determine different in the concepts achievement of physics students between classroom  implementation strategy hollywood squares learning with conventional learning classes. This type of research is a quasi-experimental, with a intact group comparison design. The sample of this research is 33 students XI IPA2 class that that appliying of strategy hollywood squares learning and 34 students XI IPA3 class that is with conventional learning . The data in this reseacrh a concept mastery score after appllyng of hollywood squares learning. The data were analyzed using descriptive and inferential statistical. From inferential statistical we found that, there were a difference  ability of the  concept achievement of physics student’s between hollywood squares learning group with conventional learning group. The result of this research olso swhowed   the concept of physics control of students in class implementation strategy hollywood squares learning that are in the medium category with a score of 70.22, while in the conventional classroom learning physics problem solving ability of students that are in the low category with a score of 63.47. thereofer,It can be concluded that the implementation of strategies hollywood squares learning can improved their understanding of physics concepts students in work and energy effort in class XI IPA at SMAN 14 Pekanbaru.